Professional development in coaching: towards a dynamic alliance of narrative and literature to transform the learning process - Christine A. Eastman (International Journal of Evidence Based Coaching and Mentoring, 2016)
Coaching draws on disciplines such as psychology, management theory, and organisational development. From these disciplines, models that seek both focused solutions to problems and those that aim to effect transformative learning have been developed. My work with students has revealed some dissatisfaction with performance coaching models such as GROW (Whitmore, 2009) and a desire to connect more with their imagination and creativity. I offer a case study of working with mature students employed by an international software company, who used a unique approach to coaching that combined narrative and literary techniques to produce coaching projects that offered solutions to work-based problems.